THE ROLE OF DIET AND PHYSICAL ACTIVITY IN RHEUMATOID ARTHRITIS TREATMENT – A REVIEW - Hanna Ćwirko; Karolina Mikołajczak; Sara Ćwirko-Kuśnierz; Martyna Różańska; Zuzanna Cudziło; Martyna Sternik; Urszula Garlak (International Journal of Innovative Technologies in Social Science, 2025)
Rheumatoid arthritis (RA) is a chronic, multifactorial autoimmune disease characterized by joint inflammation, systemic complications, and progressive disability. Pharmacological therapies such as disease modifying management (DMARDs) and symptomatic treatment (NSAIDs and GCs) remain the cornerstone of RA management, increasing evidence highlights the significant role of non-pharmacological strategies in enhancing the treatment outcomes. This review explores the impact of physical activity and diet strategies on RA progression and control. Physical activity, particularly resistance and aerobic training, improves muscle mass, joint function, and cardiovascular health, counteracting RA-related cachexia and reducing systemic inflammation. Dietary interventions, especially Mediterranean and vegan diets, are reported to have anti-inflammatory benefits due to high content of antioxidants, omega-3 fatty acids, polyphenols, and phytochemicals. Specific nutrients like vitamin D, olive oil, and polyphenol-rich foods exhibit immunomodulatory and anti-osteoclastic effects. Integrating dietary, lifestyle, and pharmacology therapies may lead to disease remission, reduce treatment resistance, and improve patients’ quality of life.